The bZIP Transcription Factor Family in Adzuki Bean (Vigna Angularis): Genome-Wide Identification, Evolution, and Expression Under Abiotic Stress During the Bud Stage - Yin, Zhengong; Meng, Xianxin; Guo, Yifan; Wei, Shuhong; Lai, Yongcai; Wang, Qiang (Frontiers in Genetics, 2022)
Adzuki bean (Vigna angularis) is an important dietary legume crop that was first cultivated and domesticated in Asia. Currently, little is known concerning the evolution and expression patterns of the basic leucine zipper (bZIP) family transcription factors in the adzuki bean. Through the PFAM search, 72 bZIP members of adzuki bean (VabZIP) were identified from the reference genome. Most of them were located on 11 chromosomes and seven on an unknown chromosome. A comprehensive analysis, including evolutionary, motifs, gene structure, cis-elements, and collinearity was performed to identify VabZIP members. The subcellular localization results showed VabZIPs might locate on the nuclear. Quantitative real-time PCR (qRT-PCR) analysis of the relative expression of VabZIPs in different tissues at the bud stage revealed that VabZIPs had a tissue-specific expression pattern, and its expression was influenced by abiotic stress. These characteristics of VabZIPs provide insights for future research aimed at developing interventions to improve abiotic stress resistance.